Buried deep and other stories - Novik, Naomi (Del Rey, 2024)
"A thrilling anthology of thirteen short stories that span the wide-ranging imagination of the New York Times bestselling author of the Scholomance Trilogy, including a sneak peek at the world where her next novel will be set"--